Synthesis and characterization of Polyurethane-based Softwood Composite as Effective Thermal Insulation with Low Density and High Mechanical Properties. (September 2020) - XIE, Yan; CHENG, Shenyu; ZHANG, Shaozheng
Highlights: A new low-density, high-flexibility, high-mechanical property cork composite (RC16) was prepared by using one-component moisture-curing polyurethane U030 as a softwood adhesive. The synthetic adhesive U030 has good compatibility and adhesion with the cork particles, and can completely wrap the cork particles and disperse uniformly. RC16 composite has a good heat resistance and can withstand high temperature ablation at 800 °C within 20 s. The effects of adhesive content, moisture content of softwood particles and curing conditions on the thermal insulation properties, flexibility, mechanical properties and ablation resistance of the materials were systematically studied, aiming to further improve theoretical basis for the preparation and application of lightweight and efficient softwood thermal protection composite materials. Abstract: In this paper, a new low-density (0.40 g/cm 3 ), high-flexibility, high-mechanical property cork composite (RC16) was prepared by using one-component moisture-curing polyurethane U030 as a softwood adhesive. The effects of adhesive content, moisture content of softwood particles and curing conditions on the thermal insulation properties, flexibility and mechanical properties of RC16 composite were investigated. The results show that the synthetic adhesive U030 has excellent compatibility and adhesion with the cork particles, and can completely wrap the cork particles and disperse uniformly. The mechanical properties of the material increase first with the increase of the moisture content of the cork particles but soon decline, and the maximum value is reached at 7.0%. With the increase of U030 content, the performance of RC16 first increased and then stabilized, while its thermal conductivity increased accordingly. When the content of U030 is 30%, the overall performance of the material is the highest; the optimum curing conditions for determining RC16 are: curing temperature 110 °C, curing time 1.5 h. RC16 composite has a good heat resistance and can withstand high-temperature ablation at 800 °C within the 20 s. The effects of adhesive content, moisture content of softwood particles and curing conditions on the thermal insulation properties, flexibility, mechanical properties and ablation resistance of the materials were systematically studied, aiming to further improve theoretical basis for the preparation and application of lightweight and efficient softwood thermal protection composite materials.